Anisotropic magnetoresistance in a Ni81Fe19/SiO2/Ca-Bi2Se3 hybrid structure - Kim, Sung Jong; Park, Youn Ho; Jang, Chaun; Hruban, Andrzej; Koo, Hyun Cheol (ELSEVIER SCIENCE SA, 2019)
A topological insulator gives a great concern in the field of thin film devices because it delivers a conducting state and a high spin-momentum locking at the material surface. To investigate the interfacial coupling between ferromagnet and topological insulator, the anisotropic magnetoresistance (AMR) in a Ni81Fe19/SiO2/Ca-doped Bi2Se3 structure is observed. The AMR is determined by the alignment between the magnetization direction of a ferromagnetic electrode and the bias current direction. The bias current induces a strong spin-momentum locking along the transverse direction which changes the magnetic anisotropy and switching process of the ferromagnetic layer. Furthermore, the angle dependence of magnetoresistance clearly shows that the amplitude of AMR is enhanced due to the coupling of Ni81Fe19/SiO2/Ca-doped Bi2Se3 hybrid structure. These results provide an efficient technique for manipulating magnetization reversal of the ferromagnetic material in spin-based devices.
Keywords: 3-DIMENSIONAL TOPOLOGICAL INSULATOR; SINGLE DIRAC CONE; BI2SE3